Uterocervical angle in predicting spontaneous preterm birth: a systematic review and meta-analysisAJOG Global Reports at a Glance - Michael Jeffrey Goldstein, MD; Jessica Marie Bailer, MD; Veronica Mayela Gonzalez-Brown, MD (Elsevier, 2023)
OBJECTIVE: This study aimed to compare the uterocervical angles in term and spontaneous preterm birth cohorts and to compare the test characteristics of the uterocervical angle and cervical length in the prediction of spontaneous preterm birth. DATA SOURCES: A systematic search of published literature from January 1, 1945, to May 15, 2022, was performed using the following databases: PubMed, Cochrane Central Register of Controlled Trials, Embase, World Health Organization International Clinical Trials Registry Platform, Web of Science, and ClinicalTrials.gov. The search was not restricted. The references of all relevant articles were reviewed. STUDY ELIGIBILITY CRITERIA: Randomized control trials, nonrandomized control trials, and observational studies were evaluated for primary comparisons. Included studies compared the uterocervical angles in term and spontaneous preterm birth cohorts and compared the uterocervical angle with cervical length in the prediction of spontaneous preterm birth. METHODS: Of note, 2 researchers independently selected studies and evaluated the risk of bias with the Newcastle-Ottawa Scale for cohort and case-control studies. Mean differences and odds ratios were calculated using a random effects model for inclusion and methodological quality. The primary outcomes were uterocervical angle and successful prediction of spontaneous preterm birth. Moreover, posthoc analysis comparing the uterocervical angle and cervical length together was performed. RESULTS: A total of 15 cohort studies with 6218 patients were included. The uterocervical angle was larger in the spontaneous preterm birth cohorts (mean difference, 13.76; 95% confidence interval, 10.61-16.91; P<.00001; I2=90%). Sensitivity and specificity analyses demonstrated lower sensitivities with cervical length alone and uterocervical angle plus cervical length than with uterocervical angle alone. Pooled sensitivities for uterocervical angle and cervical length alone were 0.70 (95% confidence interval, 0.66-0.73; I2=90%) and 0.46 (95% confidence interval, 0.42-0.49; I2=96%), respectively. Pooled specificities for uterocervical angle and cervical length were 0.67 (95% confidence interval, 0.66-0.68; I2=97%) and 0.90 (95% confidence interval, 0.89-0.91; I2=99%), respectively. The areas under the curve for uterocervical angle and cervical length were 0.77 and 0.82, respectively. CONCLUSION: Uterocervical angle alone or with cervical length was not superior to cervical length alone in predicting spontaneous preterm birth.